Beliefs underlying weight control behaviors among adolescents and emerging adults living with obesity: an elicitation qualitative study - Yu-Cheng Lin; Pei-Ching Liu; Fang-Fei Chou; I-Ching Hou; Cheng-Chen Chou; Chi-Wen Chen; Sophia H. Hu; Shu-Ping Chen; Hui-Ju Lo; Fen-Fen Huang (BMC, 2024)
Abstract Background Weight control behaviors are commonly observed among adolescents and emerging adults. However, the high prevalence of overweight and obesity in both these age groups remains an imperative health concern. Adolescents and emerging adults represent the most vulnerable groups facing the health burden of obesity. Methods This study was designed to articulate the underlying beliefs concerning weight control behaviors among adolescents and emerging adults living with obesity by an elicitation qualitative study based on the integrated behavioral model (IBM). Semi-structured and individual interviewing was utilized. Eligible participants were recruited during September and November 2020. All interviews were audio-recorded, transcribed verbatim, and analyzed using a hybrid inductive and deductive content analysis approach. Results Twenty-seven participants, comprising 12 adolescents and 15 emerging adults living with obesity, were interviewed to explore their beliefs and strategies regarding weight control behaviors. Emerging adults were more likely to engage in extreme weight control methods. Three overarching themes emerged across both age groups: eating-centered concerns, focus on physical appearance, and social interference. Significant differences were noted while adolescents and emerging adults shared some common beliefs. Emerging adults expressed more economic concerns about weight control, whereas adolescents identified food restriction as the primary barrier to their weight management efforts. These findings highlight the nuanced differences in beliefs about the weight control practice of these two developmental groups. Conclusion More beliefs-tailored and theoretically driven interventions are needed for these two unique age groups. Healthcare providers should address dietary and economic concerns while engaging adolescents and emerging adults in weight management. Future obesity interventions should incorporate shared and unique beliefs identified in each group to promote healthy weight management effectively.